2002
DOI: 10.1136/ard.61.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Weather and the pain in fibromyalgia: are they related?

Abstract: Objectives: To examine the association between fibromyalgic pain and weather to determine the nature of their interrelationship. Methods: The daily pain ratings of 55 female patients previously diagnosed with fibromyalgia were recorded on visual analogue scales (VAS) over 28 days. These ratings were then related to the official weather parameters and a composite weather variable using time series methodology. Effect sizes r were calculated from the t values and df. Results: A composite weather variable did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
4
26
0
2
Order By: Relevance
“…Table 1 summarizes the major findings of each study, showing which weather factors were involved, which of them were proved to be symptom-related and which were not (Table 1). [11][12][13][14][15][16][17][18][19][20][21][22] In Table 1 while 57% claimed to have ability to forecast weather; arthritis symptoms were significantly contributed by Beck depression score (psychological factor); the results did not prove or rule out the presence of weather-RA association OA, osteoarthritis; RA, rheumatoid arthritis; T, temperature; BP, barometric pressure; RH, relative humidity; P, precipitation; WS, wind speed; S, sunshine; DP, dew point; DPT, dew-point temperature; WVP, water vapor pressure; CC, cloud cover; SESC, The Space Environment Services Center (SESC) sunspot; SRF, solar radio flux; TH, thunderstorms; AS, average snowfall; E, evaporation. be symptom-related in 7 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the major findings of each study, showing which weather factors were involved, which of them were proved to be symptom-related and which were not (Table 1). [11][12][13][14][15][16][17][18][19][20][21][22] In Table 1 while 57% claimed to have ability to forecast weather; arthritis symptoms were significantly contributed by Beck depression score (psychological factor); the results did not prove or rule out the presence of weather-RA association OA, osteoarthritis; RA, rheumatoid arthritis; T, temperature; BP, barometric pressure; RH, relative humidity; P, precipitation; WS, wind speed; S, sunshine; DP, dew point; DPT, dew-point temperature; WVP, water vapor pressure; CC, cloud cover; SESC, The Space Environment Services Center (SESC) sunspot; SRF, solar radio flux; TH, thunderstorms; AS, average snowfall; E, evaporation. be symptom-related in 7 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, in a research about weather and pain in fibromyalgia (not included in the 12 studies), researchers used a composite daily weather variable which was calculated from indices like barometric pressure, temperature, humidity, sunlight, cloudiness etc. 21 Moreover, an earlier study which was conducted in a climate-controlled chamber showed that arthritis pain increased only when humidity increased and pressure decreased at the same time. There was no change in patients' pain perception if only one of them changed.…”
Section: Variablementioning
confidence: 99%
“…Conversely, other studies reported that weather conditions had no effect on the symptoms of rheumatic diseases [15][16][17][18][19]. Although methods of evaluation varied, all of the reviewed studies sought to answer the same question.…”
Section: Discussionmentioning
confidence: 99%
“…To date, patients suffering the following diseases: OA in other joints, rheumatoid arthritis, 3,[5][6][7][8][9][10] fibromyalgia, low back pain, migraine, tension-type headaches 8,[15][16][17][18][19][20][21][22][23] have demonstrated greater sensitivity to changes in weather with respect to pain intensity and characteristics. The patients with these diseases show more severe pain and difficulty in daily living than average TMD patients.…”
Section: -21)mentioning
confidence: 99%